Belo House at 455 S. Main Street. - Jones, Frank (Forsyth County Public Library, 2008)
Photo made in the 1950s.
Belo House at 455 S. Main Street, before it was repaired and restored.
Keywords: Digital Forsyth; Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources